Sharenting of Young Mothers in Yogyakarta: A Phenomenological Study - Fitria Fauziah Hasanah; Mela Ermawati (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
This research is motivated by the rising phenomenon of young mothers who do sharenting. Sharenting is a phenomenon of parents' habit of sharing information about their children on social media. This study aimed to identify descriptions sharenting by young mothers in Yogyakarta. This study employed descriptive qualitative research, collecting data through interviews, observations, and recordings. The data analysis technique in this study adopts phenomenological research analysis. Findings suggest that sharenting among young mothers includes young mothers sharing using social media accounts to make information about their children more accessible to others; young mothers sharenting without regard for anonymous sharing; and young mothers accidentally exposing their children's real whereabouts or full names; young mothers don't give their children veto rights over online creations; young mothers accidentally share pictures of their children undressing; and young mothers don't think the sharenting effect will affect their children's present and future state. Keywords: Sharenting, Young mothers, Early Childhood.